Age‐specific administration of chemotherapy and long‐term quality of life in stage II and III colorectal cancer patients: a population‐based prospective cohort - Jansen, Lina; Hoffmeister, Michael; Chang-Claude, Jenny; Koch, Moritz; Brenner, Hermann; Arndt, Volker (The oncologist, 2011)
After completing this course, the reader will be able to: Critically appraise the current pattern of administration of chemotherapy in older patients with colorectal cancer.Describe the survival benefits associated with chemotherapy as well as its long‐term effects on quality of life in stage II/III colorectal cancer patients.CME This article is available for continuing medical education credit at CME.TheOncologist.comTo investigate the age‐specific pattern of administration of chemotherapy and its association with long‐term survival and quality of life (QoL) in stage II and III colorectal cancer patients.Chemotherapy allocation according to disease and patient characteristics was investigated in a population‐based cohort of 562 stage II and III colorectal cancer patients. Five years after diagnosis, survival was determined and QoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 Items and a tumor specific module. The association among chemotherapy, survival, and QoL was examined while controlling for potential confounders.Chemotherapy was administered in 71% of patients aged <60 years and in only 20% of patients aged ≥80 years. A significant association between chemotherapy and longer survival time was found for stage III cancer only. Chemotherapy was associated with higher symptom levels for trouble with taste, anxiety, and hair loss. In age‐specific analyses, younger survivors (<70 years at time of follow‐up) with a history of chemotherapy reported significantly lower physical, role, and cognitive functioning and higher pain, appetite loss, hair loss, and trouble with taste symptom levels. In contrast, for older survivors (≥70 years), only two (hair loss and dry mouth) out of 38 QoL scores were significantly associated with chemotherapy.Chemotherapy is associated with lower long‐term QoL, especially in younger survivors. In cases of uncertain survival benefits of chemotherapy, consideration of its long‐term effects on QoL should be incorporated into final decisions on treatment.
Gesehen am 04.07.2022